Gold(III) Complexes: An Overview on Their Kinetics, Interactions With DNA/BSA, Cytotoxic Activity, and Computational Calculations - Radisavljević, Snežana; Petrović, Biljana (Frontiers in Chemistry, 2020)
In the last few years, metallodrugs play a key role in the development of medicinal chemistry. The choice of metal ion, its oxidation state and stability, and the choice of inert and labile ligands are just some of the very important facts which must be considered before starting the synthesis of complexes with utilization in medicinal purpose. As a result, a lot of compounds of different transition metal ions found application for diagnostic and therapeutic purpose. Beside all, gold compounds have attracted particular attention. It is well-known that gold compounds could be used for the treatment of cancer, HIV, rheumatoid arthritis (chrysotherapy), and other diseases. This metal ion has unoccupied d-sublevels and possibility to form compounds with different oxidation states, from −1 to +5. However, gold(I) and gold(III) complexes are dominant in chemistry and medicine. Especially, gold(III) complexes are of great interest due to their structural similarity with cisplatin. Accordingly, this review summarizes the chemistry of some mononuclear and polynuclear gold(III) complexes. Special attention is given to gold(III) complexes with nitrogen-donor inert ligands (aliphatic or aromatic that have a possibility to stabilize complex) and their kinetic behavior toward different biologically relevant nucleophiles, mechanism of interaction with DNA/bovine serum albumin (BSA), cytotoxic activity, as well as computational calculations.